2022
DOI: 10.5772/intechopen.101998
|View full text |Cite
|
Sign up to set email alerts
|

Social Resilience in Local Food Systems: A Foundation for Food Security during a Crisis

Abstract: The Covid-19 pandemic has presented new challenges for food production, distribution, and consumption and has exacerbated existing inequalities in access to food. However, it has also provided new opportunities for local communities to work differently, to increase collaboration, and to improve outcomes for those most in need. This chapter focuses on how various local food initiatives within a specific UK city, Preston in NW England, interact, cooperate and collaborate, and the changes to these interactions du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Previous research has demonstrated that creating informal deliberation spaces based on a particular aim can increase trust within local food systems if supported by local authorities [27]. However, seen in other cities in the UK and Europe, even if there is a commitment to integrate a systemic approach to food systems change, there is still a tendency to prioritise some issues over others, depending on local political and socio-economic conditions [31,75,76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that creating informal deliberation spaces based on a particular aim can increase trust within local food systems if supported by local authorities [27]. However, seen in other cities in the UK and Europe, even if there is a commitment to integrate a systemic approach to food systems change, there is still a tendency to prioritise some issues over others, depending on local political and socio-economic conditions [31,75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of resource availability and stability across time, it is argued that local authorities should take a leadership role in initiating, shaping, and implementing urban food governance processes [25][26][27]. Nevertheless, increased attention to the processes that lead to urban food governance mechanisms highlights that the degree of support of local authorities varies according to political will, availability of resources, and the governance culture of participation within these institutions [28,29].…”
Section: Introductionmentioning
confidence: 99%